Prognostic significance of germline BRCA mutations in patients with HER2-POSITIVE breast cancer. (October 2022) - Viansone, A.; Pellegrino, B.; Omarini, C.; Pistelli, M.; Boggiani, D.; Sikokis, A.; Uliana, V.; Zanoni, D.; Tommasi, C.; Bortesi, B.; Bonatti, F.; Piacentini, F.; et al.
Abstract: Background: HER2-positive breast cancers are rare amongst BRCA mutation carriers. No data exist regarding clinicopathological characteristics and prognosis of this subgroup of patients. Materials and methods: Using a retrospective matched cohort design, we collected data from 700 women who were diagnosed with operable invasive breast cancer from January 2006 to December 2016 and were screened for germline BRCA mutations. Clinicopathological features and survival rates were analyzed by BRCA and HER2 status. Results: One hundred and fifteen HER2-positive/BRCA mutated cases were evaluated in comparison to the three control groups: HER2-positive/BRCA wild type (n = 129), HER2-negative/BRCA mutated (n = 222), HER2-negative/BRCA wild type (n = 234). HER2-positive breast cancers were more likely to have high histologic grade and high proliferation rate than HER2-negative neoplasms, regardless of BRCA mutation status. An interaction between BRCA mutations and HER2-positive status was found to correlate with worse survival after adjusting for prognostic variables (HR = 3.4; 95% CI: 1.3–16.7). Conclusions: Co-occurrence of BRCA mutations and HER2-positive status is a poor prognostic factor in patients with early or locally advanced breast cancer. This finding may be a proof of concept that a combined pharmacological intervention directed to these targets could be synergistic. Highlights: Co-occurrence of BRCA mutations and HER2-positive status is a poor prognostic factor in patients with breast cancer. Consider an actionable role for BRCA mutations in HER2-positive disease. Combinations of PARPi plus anti-HER2 therapies are warranted in this setting.